2021
DOI: 10.21608/ejchem.2021.76599.3753
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of Ni(II) Schiff base complex on CCl4 toxicity

Abstract: Carbon tetrachloride (CCl4) is a known ecological hazardous xenobiotic that could motivate hepatotoxicity. We aimed to examine, for the first time, the therapeutic potential of nickel(II) diacetyl monoxime-2-pyridyl hydrazone complex versus CCl4induced hepatotoxicity in rats. We used six rat groups of ten animals each. The negative control, vehicle, normal rats injected i.p. with the complex (2.4 mg/kg/day), positive control rats injected i.p. with CCl4, and treated rats administered complex via injection at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…The activation of kupffer cells, which is accompanied by the generation of proinflammatory mediators, is a component of the second stage of CCl4-induced hepatotoxicity [14]. In consistent with previous studies demonstrated the alteration of biochemical markers, hepatic antioxidant status and hepatic nucleic acid content may therefore manifest of oxidative stress and cellular DNA damage caused by CCl4, Enzymatic defence mechanisms such as catalase (CAT), superoxide dismutases (SOD), and gluthatione protect cells from free radical damage (GSH) [15]. As shown in the table(1), we revealed that palm dates increased the levels of glutathione, catalase, and superoxide dismutase when compared to the positive control group Since catalase breaks down hydrogen peroxide into water and oxygen and SOD is in responsible of removing superoxide radicals, these enzymes may help regulate the redox state of plasma.This observation perfectly agrees with those of Ceci et al [16].We focused on the potential chemotherapeutic effects of palm dates in the current study, which may have been mediated through regulating the expression of MMP9 and Caspase3 in an animal model of HCC.…”
Section: Effect Of Date Fruit Extract and Cisplatin On Histological A...supporting
confidence: 61%
“…The activation of kupffer cells, which is accompanied by the generation of proinflammatory mediators, is a component of the second stage of CCl4-induced hepatotoxicity [14]. In consistent with previous studies demonstrated the alteration of biochemical markers, hepatic antioxidant status and hepatic nucleic acid content may therefore manifest of oxidative stress and cellular DNA damage caused by CCl4, Enzymatic defence mechanisms such as catalase (CAT), superoxide dismutases (SOD), and gluthatione protect cells from free radical damage (GSH) [15]. As shown in the table(1), we revealed that palm dates increased the levels of glutathione, catalase, and superoxide dismutase when compared to the positive control group Since catalase breaks down hydrogen peroxide into water and oxygen and SOD is in responsible of removing superoxide radicals, these enzymes may help regulate the redox state of plasma.This observation perfectly agrees with those of Ceci et al [16].We focused on the potential chemotherapeutic effects of palm dates in the current study, which may have been mediated through regulating the expression of MMP9 and Caspase3 in an animal model of HCC.…”
Section: Effect Of Date Fruit Extract and Cisplatin On Histological A...supporting
confidence: 61%